2008
DOI: 10.1055/s-0028-1087169
|View full text |Cite
|
Sign up to set email alerts
|

The Fatty Acid Amide Hydrolase (FAAH) Pro129Thr Polymorphism is not Associated with Severe Obesity in Greek Subjects

Abstract: Fatty amid acid hydrolase (FAAH) has been implicated at both protein and gene level with obesity. An association between Pro129Thr variant of the FAAH gene and obesity has been described, but various studies have yielded conflicting results. Our aim was to determine whether this polymorphism is related to severe obesity and whether it confers a risk for variability of quantitative metabolic traits in a cohort of Greek obese subjects. Two groups of severely obese subjects (BMI > 40 kg/m (2)) were studied: a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
4
11
0
Order By: Relevance
“…A common C358A single nucleotide polymorphism (SNP) of the FAAH has been described, producing a FAAH with defective expression. In our study, the prevalence of AA genotype (3.1%) was similar than others, for example: 3.7% (Jensen et al, 2007), 2.3% (Monteleone et al, 2008) and 1% (Papazoglou et al, 2008). The prevalence of AC genotype (28.8%) was similar than other studies; 28.1% (Jensen et al, 2007), 24.1% (Monteleone et al, 2008) and 36.5% (Papazoglou et al, 2008), too.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A common C358A single nucleotide polymorphism (SNP) of the FAAH has been described, producing a FAAH with defective expression. In our study, the prevalence of AA genotype (3.1%) was similar than others, for example: 3.7% (Jensen et al, 2007), 2.3% (Monteleone et al, 2008) and 1% (Papazoglou et al, 2008). The prevalence of AC genotype (28.8%) was similar than other studies; 28.1% (Jensen et al, 2007), 24.1% (Monteleone et al, 2008) and 36.5% (Papazoglou et al, 2008), too.…”
Section: Discussionsupporting
confidence: 67%
“…Aberle et al (Aberle, Fedderwitz, Klages, George, & Beil, 2007) have shown that carriers of the A allele had a significantly greater decrease in the triglycerides and total cholesterol levels as compared to wild type when following a low fat diet, without a relation with glucose metabolism. The lack of association between this polymorphism and anthropometric parameters has been described by other authors (Papazoglou et al, 2008). In contrast, Sipe et al (Sipe et al, 2005) evaluated BMI as a continuous variable in subjects, the median BMI was significantly higher in subjects with the A385A genotype compared to the median BMI of the other subjects.…”
Section: Discussionmentioning
confidence: 91%
“…A C358A singlenucleotide polymorphism of FAAH results in a missense mutation producing FAAH with defective expression 18 . In our study, the percentage of AC genotype (34.3%) was similar to that of other studies: 28.1 10 , 24.1 19 and 36.5%. 11 In our design, we investigated the effect of FAAH genetic variation on visfatin levels.…”
Section: Discussionsupporting
confidence: 80%
“…The novel finding of this study is the association of the C358C FAAH genotypes with lower levels of visfatin and higher levels of glucose, HOMA and insulin than of the C358A FAAH genotype, without differences in anthropometric parameters related to obesity. 19 A previous association between this polymorphism and metabolic profile has been described. Interestingly, Aberle et al 20 have shown that carriers of the A allele had a significantly greater decrease in the total cholesterol and triglycerides compared with wild type when following a low-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the human genome for possible gene variants associated with obesity led to the discovery of major obesity loci on chromosomes 2, 5, 10, 11, 16, and 20. [13][14][15][16][17][18] Differential polygenic predispositions across ethnicities could therefore explain differential development of obesity and other disease states.…”
Section: Introductionmentioning
confidence: 99%